1985
DOI: 10.1002/aic.690311103
|View full text |Cite
|
Sign up to set email alerts
|

Theory and application of an extended horizon self‐tuning controller

Abstract: A robust version of the self-tuning regulator is developed. The regulator, which requires relatively little knowledge of system characteristics (estimated order of transfer function polynomials and an upper bound for transportation delays), has been shown to yield stable control and convergence for linear, time-invariant systems. Simulations and practical tests on a large pilot-scale process have shown that the inclusion of a variable forgetting factor and an "extended horizon" control criterion provides the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 104 publications
(39 citation statements)
references
References 30 publications
0
39
0
Order By: Relevance
“…In this paper we shall study the mean-square performance of the above combination procedure (1)- (5), as well as the behavior of the following modified version: (6) where (7) with being a small positive constant. In other words, the adaptation of will continue to be given by (5) in terms of , and we shall instead set to zero or one whenever is close to the endpoints rather than limit to the values or as before.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper we shall study the mean-square performance of the above combination procedure (1)- (5), as well as the behavior of the following modified version: (6) where (7) with being a small positive constant. In other words, the adaptation of will continue to be given by (5) in terms of , and we shall instead set to zero or one whenever is close to the endpoints rather than limit to the values or as before.…”
Section: Introductionmentioning
confidence: 99%
“…More generally, on-line adaptation of certain filter parameters or even cost functions has been attempted to influence filter performance, such as adjusting the forgetting factor of recursive least squares (RLS) algorithms [6], [7] or minimizing adjustable cost functions [8]- [11]. Recently, there has been an interest in combination schemes, where the outputs of several filters are mixed together to get an overall output of improved quality [12]- [15], with some of these approaches sacrificing performance in lieu of analytical tractability.…”
Section: Introductionmentioning
confidence: 99%
“…This means that all the data in the step-response test is weighted equally in the parameter estimation algorithm. However, during the continuous update of parameters, a variable forgetting factor due to Ydstie et al [54] was the use of the variable forgetting factor helps to avoid the estimator windup, it does not guarantee that P stays bounded. Therefore, as a precaution, updating of the parameters and the covariance matrix are stopped whenever the process excitation is low or the estimation error is sufficiently small.…”
Section: Implementation Issuesmentioning
confidence: 99%
“…It was found that the variable forgetting factor of Ydstin et al [54] gave better parameter convergence, and it was used in the results presented in Table 6.12.…”
Section: Controller Parametersmentioning
confidence: 99%
See 1 more Smart Citation